The Role of Higher Education Space in Reproduction with Reflexibility of Love - Seyyedeh Sedigheh Haghighat Ziabary; Nader Ofoghi; Reza Alizadeh (توسعه اجتماعی)
Humans interact with each other to meet their needs. One of the most important of these needs is romantic interaction. Without love, much of a person's life is fruitless, and nothing is as magical as love. Romantic love exists in all cultures, and probably every culture reproduces love in its own way. In the present study, prominent social theorists on love, such as Anthony Giddens, Zygmunt Bauman, Ulrich Beck, and Elizabeth Beck Gransheim, put theories in a discourse framework using Foucault's discourse and the theory of social reproduction. Pierre Bourdieu discusses the processes of late modernity and its impact on romantic relationships, as well as reproduction with reflexibility of love through higher education. The purpose of this study is to obtain a better and more accurate sociological understanding of the social and cognitive aspects of love relationships among students with the help of the above theories. According to the mentioned purpose, the method used in this research is quantitative (survey) method. The statistical population of the present study is all students of Azad University and Gilan University of Rasht who have been studying in these two universities during the academic year 2020-2021. For sampling in this study, stratified random sampling has been used. Finally, 342 questionnaires were distributed and collected. Findings showed that there is a significant correlation between the components of higher education, social structure, and cultural structure, the prevalence of consumerist culture, intimacy crisis, students' mental structure and reproduction with reflexibility of love in higher education. Also, the results of path analysis of this research show that the reproduction of love is directly affected by mental structure (0.230), consumerism (0.198) and social structure (0.146).